Photochemical regioselective C–H arylation of imidazo[1, 2-a]pyridine derivatives using chlorophyll as a biocatalyst and diazonium salts. (19th May 2022) - Moazzam, Ali; Farid, Sara Moghadam; Khaleghi, Nima; Alizadeh, Naeimeh; Mahdavi, Mohammad
Abstract : This communication describes the development of a mild method for the arylation of imidazo[1, 2- a ]pyridine with diazonium salt derivatives and using chlorophyll as a biocatalyst via visible-light catalysis. Abstract : This communication describes the development of a mild method for the arylation of imidazo[1, 2- a ]pyridine with diazonium salt derivatives and using chlorophyll as a biocatalyst via visible-light catalysis. Natural pigments such as chlorophyll are used as a green photosensitizer and an environmentally benign catalyst. The general and easy procedure provides a transition-metal-free alternative for the formation of 2, 3-diaryl imidazo[1, 2- a ]pyridine derivatives at ambient temperature in good to excellent yields.